Sand House Therapy: Health Tourism Innovation Based on Local Wisdom through the Utilization of Sand Mattresses in Sumenep Regency - Oktaviyani, Haniza; As Sauri, Sofyan; Laora, Marisa; Sevtiana, Lily; Huzaimah, Nailiy; Hidayat, Syaifurrahman (Jurnal Abmas Negeri (JAGRI), 2025)
The community empowerment program initiated by the HIMIKA PPK Team of Wiraraja University provided a solution through the development of a Health Tourism Village known as "Sand House Therapy.” The implementation of this program consisted of three main stages: planning, implementation, and evaluation. The planning stage began with surveys, focus group discussions (FGDs), and interviews with the local community. The implementation stage involved the formation of a management team, initial data collection, the design and construction of the Sand House Therapy facilities, tourism village education, PHBS (Clean and Healthy Living Behavior) socialization, training on Sand Therapy standard operating procedures (SOPs), business management, and digital marketing, followed by the handover of assets and the official launching of Sand House Therapy. The evaluation stage included the analysis of pre- and post-test data, fulfillment of program outcomes, workshops, and regular monitoring. This HIMIKA PPK program was conducted from February 26 to October 30, 2024, by the HIMIKA implementation team of Wiraraja University. The results indicated a significant improvement in the knowledge and skills of the target group regarding tourism village development, PHBS, business management, Sand Therapy SOPs, and digital marketing. A management team was successfully formed, and a new health tourism destination Sand House Therapy was established. Through this innovation, the community of Legung Timur Village was able to optimize the use of its cultural tradition of sand mattresses and introduce this local uniqueness to domestic and international tourists.